Integrative communication model in intercultural communication on independent student exchange - Nurhadi, Zikri Fachrul; Febrina, Raden Ismira; Dalilah, Putri Aulia; Alim, Muliyati Mat (Universitas Padjadjaran, 2025)
Background: This research is motivated by the problems faced by exchange students, one of the problems is carrying out the adaptation process of cultural differences, culture, language, adaptation to the environment and communication barriers. Purpose: The aim of the research is to explain the integrative communication model in intercultural communication in the aspects of personal communication, social communication, environment, personal condition tendencies, and intercultural transformation. Methods: The research method used was descriptive method with a qualitative approach. The data collection techniques used were observation, interviews, literature study and documentation. The research subjects were determined by using a purposive sampling technique, consisting of nine informants who were independent student exchange participants from Garut University and two students from Garut Indonesian Institute of Education. Results: The results of the research show that intercultural communication in the aspect of personal communication shows attitudes and behavior of tolerance towards cultural differences, even though from a cognitive perspective they do not know yet about Garut culture. In the experience of social communication, interaction is carried out in formal and informal activities, and there are barriers due to differences in dialect and language. On the environmental side, Garut residents welcomed and accepted it well. Environmental barriers include information confusion and language difficulties. In the aspect of personal conditions, they tend not to prepare themselves by getting to know the culture in Garut, and building closeness in the process referring to personal conditions, as well as aspects of cultural transformation, the psychological conditions of independent student exchange participants. Implications: In intercultural transformation, independent student exchange participants can get used to existing cultural differences and minimize the culture shock that occurs when migrating, namely with a positive mindset. The assimilation experienced should not result in the complete loss of one’s cultural identity.